A Foreigner Who Doesn’t Steal My Job: The Role of Unemployment Risk and Values in Attitudes towards Equal Opportunities - Pecoraro, Marco; Ruedin, Didier (My University, 2016)
Immigration has become systematically politicized and opposed by many individuals. We examine individual attitudes towards equal opportunities for foreigners and Swiss citizens, using cross-sectional data from the Swiss Household Panel. Individuals with low levels of education tend to oppose foreigners, while the opposition by individuals with high levels of education increases with the risk of unemployment. Values and beliefs explain the negative attitudes of individuals with low levels of education, but not the association with the risk of unemployment for individuals with high levels of education. Clearly, both values and economic factors are important for explaining attitudes towards foreigners.
Keywords: immigration; attitudes towards equal opportunities; attitudes towards immigration; labour market competition; unemployment risk; values and beliefs